Best Cendol Café / Nur Farazulaikha Hussin - Hussin, Nur Farazulaikha (2020)
I would like to thanks to all the people who help me in finishing this case study directly or indirectly. This case study is for ENT300, so I had choose BEST CENDOL CAFÉ founded by Mr Saharuddin Bin Kuthar. The reason why I choose this business is I am strongly believe BEST CENDOL CAFÉ is one of the famous cafe in Kelantan. What make my reason strength is I have an experience working there. Before this Mr Saharuddin only grow his business only using a truck food, with the high income and profit, he grow his business by build a café. Because of his earnest attitude, BEST CENDOL CAFÉ being a focus place for people to have lunch and breakfast and already known by all the people. Mr Saharuddin success in their business by having a lot of entrepreneurial characteristic such as independent and self-confidence, information seeking and systematic monitoring and planning. By having all of this Best Cendol will grow successfully by one step to another step.